Addressing Development Disparities Between Western and Eastern Indonesia: Economic Challenges and Solutions - Suhada, Wiwin; Damayanti Rusmana, Fenny (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2025)
Indonesia faces significant development disparities between its western and eastern regions. The western regions, particularly Java, Sumatra, and Bali, have long been the center of economic growth, with more advanced infrastructure and better access to education and healthcare services. In contrast, Eastern Indonesia, including provinces such as Papua, Nusa Tenggara, and Maluku, remains lagging in various aspects of development, such as infrastructure, education, and healthcare. This study aims to analyze the economic challenges causing these disparities and explore solutions that can be implemented to reduce the development gap between these regions. The results indicate that the lack of infrastructure investment, low human capital quality, and high dependence on central government transfers are the primary factors behind these disparities. Policies such as fiscal decentralization and special autonomy in Papua have been implemented but have shown limited effectiveness. Therefore, greater investments in infrastructure and education, along with policies that promote equitable development, are needed to help Eastern Indonesia catch up and achieve more inclusive economic growth.